On-Site Measurement and Analysis of the Environmental Vibration of the Elevated Metro Lines with U-shaped Beams under Operating Conditions - NIU Xiaoli; ZHOU Yu; ZHANG Hongliang; KANG Kai; DUAN Yuzhen; LI Jingmin (Chengshi guidao jiaotong yanjiu)
[Objective] On-site measurement and analysis of the environmental vibration characteristics are conducted for the elevated metro lines with U-shaped beams under operating conditions. [Method] Taking an elevated metro line with U-shaped beams that has been in operation for 6 years in a certain city as the research object, the impacts of different train speeds, different curve radii and different vibration reduction measures on the track vibration and environmental vibration of the mentioned metro line are analyzed. [Result & Conclusion] When the train speed is between 70 and 90 km/h, for every 10 km/h increase in the train speed, the maximum Z vibration level VLZ,max at the ground strong vibration source increases by approximately 1.1 to 1.4 dB, which is in line with the recommended value of the speed correction term in the environmental impact assessment guidelines. When the line changes from straight to a 800 m radius curve and then to a 400 m one, the vibration acceleration level at the ground strong vibration source will increase by 3.7 to 4.1 dB, and the increase in the Z vibration level is slightly higher than the line correction term of 0.9 to 2.4 dB in the environmental impact assessment guidelines. The vibration reduction fasteners have an impact on the ground vibration in the frequency band from 8 to 200 Hz, the frequency at the location of the maximum difference is 50 Hz, and the vibration acceleration level is reduced by approximately 4.1 dB. The ladder-sleeper ballast bed has an impact on the ground vibration in the frequency band from 4 to 200 Hz, the frequency at the location of the maximum difference is 31.5 Hz, and the vibration acceleration level is reduced by approximately 8.2 dB. Under long-term operating conditions, the ladder-sleeper ballast bed has a better effect on reducing the vibration at the strong ground vibration source than the vibration reduction fasteners, with a wider affecting frequency band.